USING OF ADDITIONAL METHODS OF USER AUTHORIZATION - Sultanova, B.; Chsherbov, A. (Scientific Journal of Astana IT University, 2020)
The article considers the methods of additional authorization of users of information systems, their advantages, and disadvantages, typical examples of usage. Multifactor authentication is becoming a standard tool for verifying the identity and access rights of information systems, from banking operations to access to enterprise databases. With the expansion of the spheres of use of various information systems, applications, and services, users of the systems get new opportunities, convenience, and mobility. But at the same time, there is a problem of secure and controlled access, authorization and identification of the user, confirmation of his authority. The options under consideration cannot be limited to service delivery alone: mechanisms could and should be used in various combinations. In addition to the analysis, experiments were carried out on implementing and testing additional authorization mechanisms, and feedback from end users was collected. Each of the methods was evaluated from many angles: ease of implementation, ease of use by the end user, availability, and adequacy of use. At the same time, there is no way to identify the optimal and universal method of additional authorization, since various service sectors have their own requirements for accessibility, reliability, and security. One can single out corporate services that provide data exchange, data processing or analytics, or remote management services industrial network management as the most promising areas for implementation. The authors analyzed the various methods most widely used in the security market, their capabilities, advantages, and disadvantages. The authors did not set the goal of nominating one selected mechanism as a priority; therefore, no recommendations are given to use a particular method.